Negotiating Structural Vulnerability in Cancer Control - Eichelberger, Laura (Laura P.); Burke, Nancy Jean; Armin, Julie (Julie S.) (Book collections on Project MUSE., 2019)
"What can case studies about the lived experiences of cancer contribute to a burgeoning interest in the concept of structural vulnerability? And can a consideration of structural vulnerability enhance applied anthropological work in cancer prevention and control? To answer these questions the contributors in this volume explore what it means to be structurally vulnerable; how structural vulnerabilities intersect with cancer risk, diagnosis, care seeking, caregiving, clinical-trial participation, and survivorship; and how differing local, national, and global political contexts and histories inform vulnerability. These case studies illustrate how quotidian experiences of structural vulnerability influence and are altered by a cancer diagnosis at various points in the continuum of care and show that cancer is not one disease, but a set of diseases and biosocial phenomena. The contributors further utilize insights gained from the studies on cancer to extend structural vulnerability beyond its original conceptualization to encompass spatiality, temporality, and biosocial shifts in both individual and institutional arrangements"--